The Profits Directly or Indirectly Attributed to a Permanent Establishment - Gunadi Gunadi (Jurnal Pajak dan Bisnis, 2021)
This paper discussed a real case arising from the audit of a namely permanent establishment (PE) CHE operated by a CHE Ltd an enterprise residing in The People Republic of China (China).Having regular business of construction in Indonesia, this PE mantains a place of managementin Jakarta from where her businesses are managed. In 2018 this PE has finished a one-year construction project which was obtained under subcontract with an Indonesian company,namely, PT RDP at the costs of Rp 4,5 Trilyun (T). PT RDP concluded the main contract fromanother Indonesian State Owned Enterprise at the cost of Rp 5T. As this PE has alreadymaintaining a local place of management in this country, CHE PE may be called a aset-type PE‘(Gunadi, 1992, Taxation of Inbound Investment in Indonesia, APTIRC)). Most of the construtionmaterials, i.e., at least 60% of the total project costs, were imported by PT RDP from CHE Ltd (the PE‘s Head Office). This was done by Indonesian resident ompany under the import fees of 5%, as this company may claim the import facilities in respect of taxations.